Measuring the stability of the price system - Antonio Fiorencio; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
Is the high degree of indexing that characterized the Brazilian economy for decades a thing of the past, or could it be easily reactivated in the event of some important price shock? Alternatively: is the economy sufficiently stable to absorb a large exchange rate nominal devaluation? This paper propose and estimates some measures of the stability of the price system using characteristic roots of time varying parameter VAR model. We used the proposed methodology to evaluate price system stability of selected countries: Brazil, Argentina, Israel, Mexico and United Kingdom.
Keywords: 330